Gender studies science communication in periodicals (1992–2012) - Stundžė, Lijana (Information & Media, 2016)
Science helps to answer many questions while communication helps to ensure creation of new knowledge and its transformation to innovative products and services. Today, science is an inseparable part of society and science cannot exist without public attention, because it does not exist by itself. The modern society has to be informed to be able to use the research results and to make an informed and reasoned decision.The aim of the article is to analyse the gender studies formal science communication in periodicals.Generally, gender studies cover three main fields: gender, sex and sexuality; intersectionality and activism; and theoretical and methodological approaches. Gender studies is an integral part of various scientific fields: history, literature, sociology, law, communication, economics, environmental protection, and others.The article discusses the importance of science communication; analyses theoretical aspects of science communication and presents research done on gender studies science communication in periodicals.The study includes the following dimensions of analysis: topics of the publications, periodicals’ nature, institutional affiliation of the authors of the articles, and the leaders of science communication.The analysis revealed that the most popular themes in the periodicals are: women’s position in various contexts, women in science and education, women’s NGO and women’s movements. It should be noted, that the articles on gender studies topics distribution under thematic headings are inconsistent.The investigation also revealed that 37 % of the articles on gender studies have been published in a specialized bulletin “Woman’s World”, in daily newspapers “Lietuvos aidas”, “Lietuvos rytas”, “Šiaurės Atėnai”, and “Respublika”.To ensure efficient, consistent process of science communication, an integrated approach should be used: scientists should be interested in and motivated to present their research results to the public.This study covers only a small part of formal science communication – scientist to society, in order to gain a holistic gender studies science communication picture, the science communication on Internet portals, popular science festivals, events and other spaces and environments needs to be explored.
Keywords: ...